RENDAHNYA DAYA SERAP SISWA TERHADAP BUKU PAKET SENI BUDAYA BERDAMPAK PADA KUALITAS BELAJAR PADA MATA PELAJARAN SENI TARI DI SMP NEGERI 1 PARIAMAN - Novelis, Puput; Indrayuda, Indrayuda; Sudarman, Yos (SENDRATASIK UNP, 2019)
AbstractÂ This article aims to explain how the low impact of students ' absorption in the package book on the quality of learning in SMP Negeri 1 Pariaman. This type of research is qualitative research. The main instrument in this research is its own researchers and assisted with supporting instruments such as stationery, dance music and cameras. Data types use primary data and secondary data. Data collection techniques are done by observation, interviews and documentation. The steps in analyzing data are grouping data, analyzing data, describing data and creating reports. The results showed that students in grade VII. 2 have not been able to understand learning by using the package book so that students have not been able to achieve the learning process well. The low power of grade VII. 2 students in cultural art packages has an impact on the quality of student learning in dance art. This is evidenced after students have participated in learning and have not had a high desire so that the creativity of students is lacking in the spirit of learning about the book art package culture in dance learning. Lack of creativity teachers in the processing of materials that will be delivered to the students, so that the information received by students can not be absorbed in the scienceÂ Keywords: low-power students, book art package culture, quality learning art dance